Caring Economics Learning In Higher Education - Suyono, Akhmad; Fitriani, Fitriani; Megi, Anggun (Perspektif Pendidikan dan Keguruan, 2023)
The tradition of giving help to anyone has become a human habit throughout the world, it can make an extraordinary contribution to human social life, if you pay close attention there are always means to share, giving help can be done anywhere, whether in shopping areas, on the street, places of worship and media specifically aimed at victims of natural disasters, accidents, disease attacks and so on. Many social organizations are established for human welfare. Based on this phenomenon, it reflects the absence of economic concern (caring economics) in people's lives, so it is felt that there is a need for a paradigm shift from homo economicus to caring human being. Which is a human image based on a holistic approach, which recognizes the mutual need and reciprocity of various groups (Osch, 2013). This thinking can be a container for aspects of a person's behavior based on justice and altruistic values In the education curriculum in Indonesia, lecture materials related to economics in study programs have been given but are not linked to caring economics insights. So far economic learning has relatively been able to increase students' understanding of economic materials, but various facts show that teenagers (including students) face problems related to rationality in their economic behavior and lack concern for other people, the environment, and even towards herself. It is suspected that this happened partly because the content of economics lessons is still more inclined towards neo-liberalism so as to produce an understanding of how human beings do economics in their position as homo economicus. Thus economic learning needs to be directed at learning that leads to concern for fellow human beings and the environment (caring economics). This research is intended to develop caring economics learning designs for students in tertiary institutions.